Rancang Bangun Sistem Penjualan Sate Taichan Berbasis Web - Mulyadien, Muhamad Khandava; Kurniawan, Adi; Utami, Dwiarti Rahma; Enri, Ultach (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
An e-commerce Website is a Website to aims to sell one or more goods or services by using electronic media as a media for the transaction of goods/services. Taichandel is a food outlet that sells a variety of foods,  Aim of this research to solve the problem that occurs at the Taichandel because  the transaction of  this outlet still manual.  The metodh of this research using waterfall metodh, this metodh is used to  develop the software start with analytic, design, code until testing. The results of this research is  design system and system implementation with programming languages as html, php and database MySQL.  Benefit of this research is this information system can help the process of managing data related to the Taichandel Store and speed up the process of buying, selling and selling transactions  and also the owners  can check  the transaction reports because all store data is stored in the database so as to maximize sales evaluation and minimize loss of sales data.